Dynamically Tunable Singular States Through Air-Slit Control in Asymmetric Resonant Metamaterials - Yeong Hwan Ko; Robert Magnusson (Photonics)
This study presents a novel method for dynamically tuning singular states in one-dimensional (1D) photonic lattices (PLs) using air-slit-based structural modifications. Singular states, arising from symmetry-breaking-induced resonance radiation, generate diverse spectral features through interactions between resonance modes and background radiation. By strategically incorporating air slits to break symmetry in 1D PLs, we demonstrated effective control of resonance positions, enabling dual functionalities including narrowband band pass and notch filtering. These singular states originate from asymmetric guided-mode resonances (aGMRs), which can be interpreted by analytical modeling of the equivalent slab waveguide. Moreover, the introduction of multiple air slits significantly enhances spectral tunability by inducing multiple folding behaviors in the resonance bands. This approach allows for effective manipulation of optical properties through simple adjustments of air-slit displacements. This work provides great potential for designing multifunctional photonic devices with advanced metamaterial technologies.